Theoretical Models for Video on Demand Services on Peer-to-Peer Networks. (9th September 2009) - Branca, Giovanni; Schierl, Thomas; Atzori, Luigi
Abstract : Peer-to-peer networks (P2Ps) are becoming more and more popular in video content delivery services, such as TV broadcast and Video on Demand (VoD), thanks to their scalability feature. Such characteristic allows for higher numbers of simultaneous users at a given server load and bandwidth with respect to alternative solutions. However, great efforts are still required to study and design reliable and QoS-guaranteed solutions. In this paper, within the scenario of P2P-based VoD services, we study the phenomenon of peer churns and propose four models of the peer behaviour to evaluate its impact on the system performance, which are based on the Gilbert-Elliot chain, the fluidic representation of the user behavior, and a queuing analysis of the system. The models are compared by computing the resources the system has to add on top of the P2P network to satisfy all the download requests. Simulations show important relationships between playback buffer length, peer request rate, peer average lifetime, and server upload rate.